2009
DOI: 10.1111/j.1524-4741.2009.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Role of External Breast Prostheses After Total Mastectomy

Abstract: After total mastectomy, many women choose to wear external breast prosthesis rather than undergo breast reconstruction. The purpose of this study was to evaluate long-term satisfaction among external breast prosthesis wearers and the impact of satisfaction on prosthesis use. A questionnaire was designed to assess demographic information, prosthesis information provision, prosthesis use, and satisfaction with prosthesis. Fifty-nine women who had undergone total mastectomy without breast reconstruction completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 20 publications
1
17
0
5
Order By: Relevance
“…Not wearing an external breast prosthesis can result in bone deformities and abnormal body axis [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Not wearing an external breast prosthesis can result in bone deformities and abnormal body axis [26]. …”
Section: Discussionmentioning
confidence: 99%
“…All were satisfied. However, those who were more than five years post-mastectomy were more satisfied than those who were less than five years (90% versus 67%) and those who wore the prosthesis consistently (six to seven days/week) were more satisfied than those who only wore it only in public (89% versus 50%) (Glaus & Carlson, 2009). In Ireland, a survey of breast cancer survivors (N = 627) concluded that women considered the breast prosthesis as important because it enhanced their shape, appearance, sense of well-being, confidence, and femininity (Gallagher, Buckmaster, O'Carroll, Kiernan, & Geraghty, 2010).…”
Section: Introductionmentioning
confidence: 91%
“…The difficulties in seeking information about breast prostheses, locating a vendor, and being fitted for a prosthesis were issues for these Canadians, just as they had been for women in other countries (Gallagher et al, 2010;Glaus & Carlson, 2009;Roberts et al, 2003) and added to the emotional distress women felt. It is disappointing to learn there is so much variation in these processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prosthesis should be comfortable to wear for long periods during the day and help to maintain good posture by counteracting the weight of the remaining breast. 5 Studies have shown that satisfaction is significantly associated with how well the prosthesis fits, the weight and movement. 6,7 Traditionally, prostheses are available commercially as 'off the shelf' in a range of sizes or are custom made, typically by maxillofacial prosthetists.…”
Section: Introductionmentioning
confidence: 99%